L-Ascorbic Acid-g-Polyaniline Mesoporous Silica Nanocomposite for Efficient Removal of Crystal Violet: A Batch and Fixed Bed Breakthrough Studies - Imran Hasan; Ibtisam I. BinSharfan; Rais Ahmad Khan; Ali Alsalme (Nanomaterials, 2020)
In the present study, mesoporous silica nanoparticles (MSNs) synthesized through sol–gel process and calcined at 600 °C were further surface functionalized by a copolymer chain of L-ascorbic acid (AS) and polyaniline (PAni) by in situ free radical oxidative polymerization reaction. The surface modification of MSNs by AS-g-PAni was confirmed by using various analytical techniques, namely FTIR, XRD, SEM–EDX, TEM and AFM. The composition of AS-g-PAni@MS was found to be composed of C (52.53%), N (20.30%), O (25.69%) and Si (1.49%), with 26.42 nm as the particle size. Further, it was applied for the adsorption of crystal violet (CV) dye under batch, as well as fixed bed method. RSM–BBD was taken into consideration, to optimize the various operational parameters effecting the adsorption through batch method. To explore maximum efficiency of the material, it was further subjected to adsorption of CV under fixed bed method, using the variable bed heights of 3.7, 5.4 and 8.1 cm. Based on high value of regression coefficient (R2) and low value of RMSE given as (0.99, 0.02) for 3.7 cm, (0.99, 0.03), the breakthrough data were very well defined by the Thomas model, with optimum concurrence of stoichiometric adsorption capacity values. The external mass transfer equilibrium data were well fitted by the Langmuir model, with maximum monolayer adsorption capacity of 88.42 mg g−1 at 303 K, 92.51 mg g−1 at 313 K, 107.41 mg g−1 at 313 K and 113.25 mg g−1 at 333 K. The uptake of CV by AS-g-PAni@MS was well defined by pseudo second order model with rate constant K2 = 0.003 L mg–1 min–1 for 50 and 0.003 L mg–1 min–1 for 60 mg L–1 CV. The adsorption reaction was endothermic with enthalpy (ΔH) value of 3.62 KJ mol−1 and highly efficient for treatment of CV-contaminated water for more the five consecutive cycles.